2018
DOI: 10.5897/jdae2017.0841
|View full text |Cite
|
Sign up to set email alerts
|

Use of a warrantage system to face rural poverty and hunger in the semi-arid area of Burkina Faso

Abstract: It is widely believed that limited access of small scale farmers to agricultural credit is one of the key causes of rural poverty and a major constraint to adoption of innovations in Sub-Saharan Africa. Since the early 1960s, many strategies to access agricultural credits have been implemented with success. This study assessed the effects of warrantage, a community-based micro credit system, on poor small resource farmers' income and livelihoods of the semi-arid area of Burkina Faso. Two broad socio economic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Besides, FECECAM tailored its loan products to the need of its client. For example, the lender offers among its farm loan products, the warrantage and an inventory credit system that remains the main source of funds for agricultural activities in Sub-Saharan countries like Burkina Faso (Ouattara et al, 2018). Studies showed that the warrantage, a community-based microcredit scheme, is suitable and affordable to poor small-scale farmers (Ouattara et al, 2018;Tabo et al, 2011).…”
Section: Impact Of Agricultural Loansmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides, FECECAM tailored its loan products to the need of its client. For example, the lender offers among its farm loan products, the warrantage and an inventory credit system that remains the main source of funds for agricultural activities in Sub-Saharan countries like Burkina Faso (Ouattara et al, 2018). Studies showed that the warrantage, a community-based microcredit scheme, is suitable and affordable to poor small-scale farmers (Ouattara et al, 2018;Tabo et al, 2011).…”
Section: Impact Of Agricultural Loansmentioning
confidence: 99%
“…For example, the lender offers among its farm loan products, the warrantage and an inventory credit system that remains the main source of funds for agricultural activities in Sub-Saharan countries like Burkina Faso (Ouattara et al, 2018). Studies showed that the warrantage, a community-based microcredit scheme, is suitable and affordable to poor small-scale farmers (Ouattara et al, 2018;Tabo et al, 2011). A study by Ouattara et al (2018) showed that the warrantage system's use improved farmers' profit by 140%, resulting in higher income, ultimately improving farmers' livelihood.…”
Section: Impact Of Agricultural Loansmentioning
confidence: 99%
See 1 more Smart Citation
“…Agricultural sector in the Benin Republic actors since its essence is to create a conducive environment; thanks to the horizontal and vertical in-between links it builds among actors of MSP that brings together value chain core actors, non-financial service providers and partakers of financial sector who, through their knowledge of a chain's specific risks, design a tailor-made credit scheme. Promoted by FAO (Ouattara et al, 2018), this approach has gradually been experienced in the Republic of Benin for more than a decade. Yet, to the best of our knowledge, very little is known about key drivers of access to formal credit as well as the amount received in that context of VCFS.…”
mentioning
confidence: 99%